Modeling of embankment on soft soils using numerical analysis with various soil models / Rohamezan Rohim, Ir. Hj Mohd Farid Ahmad @ Majid and Dipl.-Ing(FH). Mohd Zaini Endut - Rohim, Rohamezan; Ahmad @ Majid, Mohd Farid (Ir. Hj); Endut, Mohd Zaini (Dipl.-Ing(FH). ) (2005)
Numerical analysis used in engineering field has enhanced the performance of the work effort. By using the latest technology such as PLAXIS (Finite Element Code For Soil And Rock Analyses) it help engineers to predict what will happen to the soils (especially soft soil) in future. Even it also can see what really happen in the past, why the soil fail after construction. In this study, the failure of the embankment after being construct on the soft soil has trigger the big problem. The soil failed during the construction stage and it is found that the fill used is not suit able added to the unpredictable strength of the ground soil. The study tried to simulated the behaviour of the embankment on the soft soil by lied the fill layer at five stages of construction. This is equivalent to the total 45 days work expected to being carried out by the contractor. In actual case the embankment seem to fail during the construction . Mohr Coulomb model, Soft Soil Model and Soft Soil Creep Model has been used to simulated the behaviour of the failure embankment. It is found that in certain cases Mohr Coulomb agreed with the result produce by the contractor.